Synergizing Soil Restoration and Circular Economy: Integrated Application of Nano-particle Enhanced Compost (NEC) and Husk Charcoal - Suyani, Ida Sugeng; Nurhidayati, Nurhidayati; Hartanti, Aprilia; Oktaviani, Dewi Anggun; Susyanti, Jeni; Tito, Sama’ Iradat; Rahmansyah, Ahmad Iskandar (IMPOWERMENT SOCIETY, 2026)
The progressive decline in rice productivity, currently reaching 7–8 tons/ha in Klaseman Village, is primarily attributed to soil fertility degradation resulting from the intensive and long-term application of inorganic chemical fertilizers. This environmental challenge necessitates a strategic technology transfer to remediate soil health and enhance farmer self-sufficiency through sustainable practices. This community service initiative aimed to elevate the technical proficiency and managerial capacity of the "Gotong Royong I" Farmer Group in the production and systematic application of Nano-particle Enhanced Compost (NEC). Utilizing a participatory approach, the program integrated theoretical socialization, hands-on manufacturing practice, and intensive field mentoring on a 0.5-hectare demonstration plot involving 25 participants. Empirical results demonstrate that 100% of the participants achieved mastery in independent NEC production, successfully generating 400 kg of the enhancer. Field implementation facilitated a 50% reduction in conventional chemical fertilizer dosage while yielding superior vegetative growth and improved soil vitality compared to control plots. Ultimately, this program effectively bridges the gap between laboratory innovation and community adoption, establishing a circular economy model that supports long-term agricultural sustainability.